Pengembangan Taman Kota dengan Outdoor Coworking Space Pasca Pandemi Covid-19 - Bayuadi, Muhammad Widad (Universitas Sebelas Maret Surakarta, 2020)
In the state of the covid 19 scourge currently sweeping the world, adaptation is a concern for any element especially in public activity space and room. This study addresses to obtain research results regarding an urgency of need for public space with all its elements and facilities that support productive culture of students & workers in the industrial world 4.0, especially in Indonesia. This study uses descriptive qualitative methods with analysis of field observations, questionnaires, descriptive, and literature studies. The statistical method used is using ordinal variable measurement. These results and research are the basis that it is necessary and urgent of outdoor coworking space to carry out further and in-depth research on contextual and cultural appropriateness so that it is appropriate to be applied and become a support in Indonesia's preparation to compete with the global world in the 4.0 Industrial Revolution Era and post-covid adaptation of social interaction in Nganjuk City Park.